Analysis Analysis of P5 Implementation in Character Building of Students in Sekolah Penggerak: Analysis of P5 Implementation in Character Building of Students in Sekolah Penggerak - Kumalasari, Evadwi; Fatimah, Nur; Lisnawati, Santi (TA`DIBUNA, 2026)
This research explores the implementation of P5 in shaping student character within the Sekolah Penggerak program. The study aims to determine the effectiveness of P5 in instilling Pancasila values among students. A quantitative survey methodology was employed, using a sequential explanatory mix model. Data was collected from 550 students in 5 Subang Regency's Sekolah Penggerak. The results indicated that P5 has a significant positive impact on developing students' character, with improvements observed in dimensions such as Faith, Devotion to God Almighty, Global Diversity, Mutual Cooperation, Critical Thinking, Independence, and Creativity. Specifically, 72% of respondents demonstrated good character, and 17% showed very good character. The conclusion is that the P5 project, with its project-based learning approach, effectively promotes conscious and meaningful learning, contributing to the formation of the Pancasila student profile.